Alteration of cholinergic pressor and antinociceptive responses in rats pretreated with the cholinergic toxin AF64A - (:unkn) unknown (My University, 1998)
1. In the present study, the pressor and antinociceptive effects of physostigmine and oxotremorine were investigated in rats injected with AF64A intracerebroventricularly. 2. Physostigmine (50-100 micrograms/kg, i.v.)-induced pressor responses were significantly lower in AF64A-injected rats compared with saline-injected animals, whereas oxotremorine (20-80 micrograms/kg, i.v.)-induced responses were found to be similar to those seen in the saline group. 3. The physostigmine (100 micrograms/kg, s.c.)-induced antinociceptive effect was totally abolished by AF64A treatment, but that of oxotremorine (30 micrograms/kg, s.c.) remained unchanged at the tail-flick test. 4. The results of this study present functional evidence for AF64A-produced substantial loss of cholinergic neurons involved in the regulation of blood pressure and nociception but not in postsynaptic muscarinic receptors.
Keywords: Female; Animals; Male; Rats; Choline; Pain Measurement; Rats, Sprague-Dawley; Avoidance Learning; Cholinesterase Inhibitors; Physostigmine; Muscarinic Agonists; Oxotremorine; Analgesia; Aziridines; Maze Learning; Neuromuscular Blocking Agents